Strategi Pengembangan Usaha Mikro Kecil Menengah di Kube Kuliner Asahan pada Masa Pandemi Covid-19 - Miliantari, Dea; Nawawi, Zuhrinal M; Nasution, Juliana (Universitas Muhammadiyah Sumatera Utara, 2022)
The development strategy is an internal analysis of regional market conditions, including strengths and weaknesses, as well as external market conditions, future opportunities and threats, and then the adoption of alternatives to determine the Strategies that must be implemented to maintain business stability during the Covid19 pandemic. This type of research uses descriptive qualitative research. The analysis used is a logic-based SWOT analysis that uses the IFAS matrix, EFAS matrix, SWOT matrix, and Grand Strategy matrix to maximize profits, opportunities, losses, and threats. The results of this study indicate that the strategy used by culinary msme in Asahan Culinary Kube during the Covid19 pandemic is in the Type 1 (aggressive) quadrant, which is a position that is profitable and has high potential. Based on an internal strategy analysis with a total score of 2.08 and a total score of 2.34 for external factors, it means that culinary msme in Asahan Culinary Kube can take advantage of existing opportunities to implement them during the Covid19 pandemic, a strategy that supports aggressive growth.Keywords : Development Strategy, Culinary Msme, Covid-19, SWOT Analysis.